Analysis of Mustard and Sunflower oil available in local market of Baglung Bazaar - Budhathoki, Narendra; Punmagar, Mira (Pragnya Sarathi, 2024)
Two types of oil, including mustard oil and sunflower oil, were gathered for the study from the Baglung bazaar. Five separate physical-chemical characteristics, including moisture content, saponification value, acid value/free fatty acid, iodine value, and peroxide value, were determined. Consumer opinions were collected through a structured questionnaire on these edible oils. The physicochemical data were compared to the normative values advised by the Department of Food Technology and Quality Control (DFTQC), Babarmahal, Kathmandu, Nepal. For mustard oil and sunflower oil, the moisture content was found to be 0.24% and 0.38% respectively, which was greater than the standard value of 0.20%. The saponification value was found to be 157.64 mg KOH/g for mustard oil and 164.37 mg KOH/g for sunflower oil. For mustard oil and sunflower oil, the range of the acid value was 2.24 mg KOH/g and 3.36 mg KOH/g respectively. The iodine values of mustard oil and sunflower oil were found to be 107.95 and 125.60 g /100 g respectively. Finally, the peroxide values for mustard oil and sunflower oil were found to be 4 and 6 meq/kg respectively. Except for moisture content, the other parameters fell within permitted values. The study's findings indicate that all of the oil samples are of acceptable grade and are safe for consumption by humans.